2019
DOI: 10.1371/journal.pone.0226853
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feasibility of NGS liquid biopsy analysis in NSCLC patients

Abstract: BackgroundAnalysis of circulating tumor nucleic acids in plasma of Non-Small Cell Lung Cancer (NSCLC) patients is the most widespread and documented form of "liquid biopsy" and provides real-time information on the molecular profile of the tumor without an invasive tissue biopsy.MethodsLiquid biopsy analysis was requested by the referral physician in 121 NSCLC patients at diagnosis and was performed using a sensitive Next Generation Sequencing assay. Additionally, a comparative analysis of NSCLC patients at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 66 publications
(73 reference statements)
3
29
2
Order By: Relevance
“…Moreover, the concordance was significantly higher in patients at diagnosis than in patients at progression, being 88.9% and 70.2%, respectively [ 24 ]. In contrast, a 60–70% overall concordance rate has been reported in studies in which all the genetic alterations identified in tumor specimens and plasma samples were considered, including TP53 and KRAS mutations [ 39 , 40 , 51 , 53 ]. Importantly, the overall concordance rates were higher when the time elapsed between tissue and plasma sampling was short (62.5% vs. 43.3%; cut-off 1.3 months) [ 51 ].…”
Section: Ngs-based Cfdna Analysis For Guiding Precision Medicine Imentioning
confidence: 99%
“…Moreover, the concordance was significantly higher in patients at diagnosis than in patients at progression, being 88.9% and 70.2%, respectively [ 24 ]. In contrast, a 60–70% overall concordance rate has been reported in studies in which all the genetic alterations identified in tumor specimens and plasma samples were considered, including TP53 and KRAS mutations [ 39 , 40 , 51 , 53 ]. Importantly, the overall concordance rates were higher when the time elapsed between tissue and plasma sampling was short (62.5% vs. 43.3%; cut-off 1.3 months) [ 51 ].…”
Section: Ngs-based Cfdna Analysis For Guiding Precision Medicine Imentioning
confidence: 99%
“…Nucleic acid purification is a crucial step also for liquid biopsies and it can be hampered by an inappropriate plasma separation, most studies directly use ctDNA [ 24 , 65 ], but in some cases gene fusion analysis requires ctRNA and specific purification procedures [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…This assay allowed to characterize ALK, ROS1 and RET fusions together with the most common genetic alterations by preparing a ctDNA and a ctRNA library. Moreover, such an assay uses random molecular tags as a unique molecular identifier to uniquely label each molecule prior to library amplification, thus increasing the test performance [ 66 ].…”
Section: Data Sourcesmentioning
confidence: 99%
“…The first approach is limited by the uncommonness of cancer cells in the bloodstream (around one CTC per billion blood cells) [ 162 ], which significantly reduce the clinical application of this method. Alternatively, analysis of nucleic components of tumor cells—cell free DNA (cfDNA) and circulating RNA (circRNA, including miRNA)—is gaining an increasing interest, demonstrated in numerous studies and clinical trials [ 159 , 163 , 164 , 165 ]. Rapid advancement of novel technologies, enables to detect cancerous DNA/RNA with high accuracy for diagnosis, prognosis and therapeutic monitoring [ 166 ].…”
Section: Applications Of Transcriptome Analysis In Oncologymentioning
confidence: 99%